The Influence of Emotional and Rational Factors on Customer Decisions in Choosing Islamic Banking Services - Nur Haya; Pratiwi, Indah; Sultan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The purpose of this study is to understand the factors that influence customer decisions in choosing Islamic banks in Indonesia. The study used a quantitative method, by distributing questionnaires to respondents, the type of data used is primary data from 153 respondents who are Islamic bank customers. The sampling technique used was incidental sampling, and data analysis was carried out using multiple linear regression, classical assumption tests, hypothesis tests, and descriptive statistics, using SPSS version 27. The results of the study indicate that emotional and rational factors individually have a positive impact on customer decisions for the t-test, while for the f-test simultaneously, both also significantly influence customer decisions.